Autocuidado de la salud en trabajadoras del sector informal en Guadalajara (México) Una perspectiva de género. - Estrada, Mónica Contreras; Baltazar, Raquel González; Cortes, Silvia León; Rodríguez, Guadalupe Aldrete; Santacruz, Gustavo Hidalgo (Salud Uninorte)
Objectives: The aim of this study was to explore the social meaning of health self-care for women in the informal sector (street market or "tianguis") a gender perspective. Subjects and methods: This was a qualitative study based on the theory of social meanings. Design: A Case Study. Techniques used: field observation and interviews with 6 women in informal work three "tianguis". Selected by purposive sampling. They were recorded and analyzed through thematic content analysis supported by Atlas Ti. Results: Emphasizes that women expressed a desire to change their lives, saying that they feel worried, tired and stressed. They indicate that in this kind of work there are feelings of happiness, love and joy. In the domain of the meaning of health they said they are healthy, but they justified and symbolize as anger not having time for medical checkup. Conclusion: From this perspective, participants make visible this work as not well recognized and sacrificed as well. They indicate that they are willing to receive information to be better in their families and keep fighting against all odds of inequality, injustice and inequality at work.